2020
DOI: 10.3390/nu12071994
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and Micronutrients Adequacy in Women of Childbearing Age: Results from ELANS Study

Abstract: Dietary diversity, an important component of diet quality, is associated with an increased probability of adequate micronutrient intake. Women of childbearing age (WCA) are particularly vulnerable to micronutrient inadequacy. The Minimum Dietary Diversity for Women (MDD-W) has been used widely as a proxy measurement of micronutrient adequacy. This study aimed to assess the association between MDD-W and nutrients adequacy among WCA of eight Latin American countries. Nutrient intakes from 3704 WCA were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 40 publications
7
33
1
2
Order By: Relevance
“…MARs were compared by age group, country, SES, weight status and dietary quality scores accomplishment. DDS has been previously validated as a proxy of micronutrients adequacy in women from the ELANS study sample [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…MARs were compared by age group, country, SES, weight status and dietary quality scores accomplishment. DDS has been previously validated as a proxy of micronutrients adequacy in women from the ELANS study sample [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…In China, high energy intake reporting was rare. As in Mexico, low energy intake reporting increased markedly with BMI, and in the case of China it was also high among children 6-17 years 10 who reported that they were on a weight-loss diet. The pattern of low energy intake reporting by age differed from that of Mexico, with the highest prevalence for young children (2-4 years of age) and older adolescents (15-19 years of age).…”
Section: Analyses Excluding Low and High Energy Intake Reportersmentioning
confidence: 96%
“…The underlying 10-point score is also associated with micronutrient adequacy. The indicator was developed based on analyses of data from nine sites in six countries (five low-income and one lower-middle-income); subsequently, associations between MDD-W (and/or its underlying score) and nutrient intakes and adequacy have been demonstrated in a number of studies from diverse contexts (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Background and Objectives Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, in LatAm and other western countries, a high proportion of dietary vitamin E is provided by fats and oils, together with sweet baked products, none of which are rich in α-tocopherol but contribute to α-tocopherol intake because of their high consumption. In agreement, a recent report showed that Latin American women of childbearing age consumed diets with low diversity of nutrients, characterized by high intake of cereals and low consumption of vitamin E-rich foods such as green leafy vegetables (6.8%) and nuts or seeds (2.8%) [56]. Dietary diversity usually reflects the high quality of the diet and is associated with an increased probability of adequate micronutrient intake [57].…”
Section: Discussionmentioning
confidence: 79%